TINJAUAN YURIDIS TERHADAP HAK ATAS PENSIUN SEBAGAI JAMINAN HUTANG PADA BANK PEMBANGUNAN DAERAH CABANG SAMARINDA - Triaji, Triaji (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRAK In essence, granting credit with the right to the retirement of this pension, its retirement does not suffer from the fact that the installment of the loan is directly deducted by the State Treasury Office in this case the Post Office designated under the pension deduction authorization sent by BRI Samarinda Branch. But that does not mean giving credit with the right to retirement there is no obstacle that inhibits the smooth recovery of credit at BRI Samarinda Branch. This is evident in the presence of some borrowers who are in arrears in credit payments. The reason for the delinquency is that the borrower has defaulted and has overmacht.           The efforts made by banks in this case of Bank Rakyat Indonesia Samarinda Branch in settlement of outstanding loans are as follows: For pensioners who suffer from defaults due to unpaid retirement, the effort will be done by BRI Samarinda branch is to see how much when he delays when the arrears have happened three times consecutively, the bank will go to the Post Office where the customer is usually taking the retirement money to be asked for an explanation of what causes the unpaid installment at BRI Branch Samarinda. After knowing what causes the unpaid installment, the bank will come to the address of the borrower to give a warning or warning that late payment of the installment will harm the customer himself. Bank efforts for the deceased borrower, first see or need to know the age of the borrower. This is done considering that the age of the borrower affects and determines which insurance guarantees the pension recipient. Therefore if there is a borrower who dies while his credit is not yet paid, then the Bank Rakyat Samarinda Branch's effort is to make a claim against the insurance where the decision is his dependent on the age of the borrower. The submission of this claim is based on the actual balance that coincides with the month of the retiree's death.  Keyword : credit,pension,installment